Measurement of Thromboxane Biosynthesis in Health and Disease - Patrono, Carlo; Rocca, Bianca (Frontiers in Pharmacology, 2019)
Thromboxane (TX) A2 is a chemically unstable lipid mediator involved in several pathophysiologic processes, including primary hemostasis, atherothrombosis, inflammation and cancer. In human platelets, TXA2 is the major arachidonic acid derivative via the cyclooxygenase (COX)-1 pathway. Assessment of platelet TXA2 biosynthesis can be performed ex vivo through measurement of serum TXB2, an index of platelet COX-1 activity, as well as in vivo through measurement of urinary enzymatic metabolites, a non-invasive index of platelet activation. This review article describes the main findings of four decades of clinical investigation based on these analytical approaches, focusing on the measurement of TXA2 metabolites to characterize the pathophysiologic role of transiently or persistently enhanced platelet activation, and to describe the clinical pharmacology of COX-1 inhibition in health and disease.